Kandungan Kolesterol Kepiting Bakau (Scylla serrata) Jantan Dan Betina Pada Lokasi Yang Berbeda - Pramudya, Tunas Pulung; Suryono, Chrisna Adhi; Supriyantini, Endang (977-2407769)
Mud crab (Scylla serrata) have potency commercial market in this country and the other country. That thing because mud crab (Scylla serrata) flesh has a delicious taste and high nutrition. People haven’t knowed about cholesterol content in both male or female mud crab (Scylla serrata), whereas the knowledge about cholesterol content is important to consider nutrition intake to keep in good health. This research aim to determine cholesterol content in Scylla serrata by observing male and female crab in Pemalang and Demak. This research used descriptive method and sampling used purposive random sampling method. Determination of sampling position used purposive sampling method. This research has done in October 30th – November 25th 2011. This research used 30 male and 30 female with mean body weigh 60 - 100 g. Analysis of cholesterol content used method by Lieberman–Burchad. Result from this research indicates that S. serrata from Pemalang has cholesterol content more large than S. serrata from Demak, while the male crab from both place has higher cholesterol content than female crab (66,67 mg/100g and 61,67 mg/100g in male crab, and 64,67 mg/100g and 58,33 mg/100g in female crab).